(untitled) (Latakia University Journal -Basic Sciences Series, 2019)
In this research we study the single-particle with particle-rotor model of the 12,69161Tm,69159Tm,69163Tm"> isotopes. The rotational energy of the nucleus related to its orientation . This model study the nucleus as a tow parts ; one of them is the core which is moving in a collective motion, in addition of the other part of motion which is the single particle motion outside the core. The calculation shows that adding the coriolis effect make a better agreement to the experimental values of the energy than the calculation without the coriolis effect the research suggestion adding the vibration motion which contributes in the core vibration.